ANALISIS KEPUASAN KONSUMEN KERUPUK UBI DI KECAMATAN PANGEAN KABUPATEN KUANTAN SINGINGI - Indra Putra; Jamalludin Jamalludin; Nariman Hadi (Indonesian Journal of Agricultural Economics, 2019)
The purpose of this study was to determine the interests and performance and also satisfaction of consumers Hanum cassava crackers in Pangean District. The method used in this research was the Importance And Performance Analysis (IPA) and the Consumers Satisfaction Index (CSI) analysis. The average results obtained from the level of importance that is equal to 103.40 with the criterion score of importance, and the level of performance that is equal to 97.40 with the score criteria satisfied. And the result of satisfaction or consumer satisfaction index of cassava crackers was 81.20%, where this value was in the range of consumer satisfaction index of 75% -100% which  the criteria score was very satisfied. Based on the Cartesian diagram, in quadrant I. Quadrant II means atribute are considered important and have good performance, and there are 3 attributes occupying this quadrant namely the price, taste and cleanliness. In quadrant III (low priority) means consumers feel less important but the atribute can still be improved the performance,  there are 2 attributes that occupy on it, namely the aroma and size attributes. Quadrant IV means excessive, where it was assumed that the level of importance was low but the level of performance was high. There were no attributes occupying on this quandrant.